Land Drainage Technology - Canada's Leadership Role - Irwin, Ross (Scientia Canadensis, 1989)
ABSTRACTLand drainage technology remained static from the days of the Pharaohs to 1900. Practical drain installation machinery was introduced just prior to 1900 and was gradually improved to the 1960s. From 1850, clay drain tile were manufactured in hundreds of small rural plants in Ontario. These tile were installed by hand or by open trench machinery. In the late 1960s land drainage technology advanced rapidly with the introduction of plow-in equipment and the parallel development of corrugated plastic drainage tubing. Laser technology was introduced to make the operation efficient. The design, construction, and world-wide sale of this new equipment began in Ontario and has developed major side industries such as the production of tubing for veins and arteries of humans. The paper discusses the development of the technology using four time periods.